ダイ 24 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1983 - 塚村, 浩二; ツカムラ, コウジ; 矢野, 隆夫; ヤノ, タカオ; 近藤, 幸治; コンドウ, コウジ; 岩下, 剛己; イワシタ, ゴウキ; Tsukamura, Koji; Yano, Takao; Kondoh, Kouji; Iwashita, Gouki (1988)
P(論文) この報告は第24次南極地域観測隊越冬隊気象部門が, 1983年2月1日から1984年1月31日まで, 昭和基地において行った気象観測, 主として地上および高層気象観測の結果をまとめたものである。観測は総合自動気象観測装置(AMOS)を使用し, 観測値・統計値の自動処理を行った。その他の観測項目や結果の取り扱いは第23次観測隊と同じである。成層圏における年平均気温の低下傾向やオゾンゾンデ観測による10月のオゾン量減少に特徴が見られる。 This paper describes the results of meteorological observations, mainly surface and aerological, from 1st February 1983 to 31th January 1984 at Syowa Station, carried out by Meteorological Observation Team of the 24th Japanese Antarctic Research Expedition (JARE-24). The observations and the statistic data were automatically processed by using Automated Meteorological Observation System (AMOS). Procedures for other observation items and the results are same as those conducted by JARE-23. Remarkable characteristics : Tendency of falling annual mean temperature in the stratosphere and reduction of ozone quantity in October. departmental bulletin paper